Pengaruh Tax Avoidance, Kepemilikan Institusi dan Kinerja Keuangan terhadap Harga Saham - Niken Tri Mulatsari; Anita Wijayanti; Yuli Chomsatu Samrotun (Ekonomis: Journal of Economics and Business, 2020)
The stock price will affect someone to invest in a company. This study aims to determine whether the influence of tax avoidance, institutional ownership and financial performance on stock prices. This financial performance measurement uses the proxy of Net Profit margin (NPM) and Earning Per Share (EPS) of real estate companies listed on the Indonesia Stock Exchange in 2017-2018. The population used in this study is real estate companies listed on the Indonesia Stock Exchange 2017-2018. The samples used were 33 real estate companies. This type of research data is secondary data obtained from the financial statements of real estate companies listed on the Indonesia Stock Exchange 2017-2018. To process and analyze data, the writer uses Descriptive Statistical Analysis, Multiple Regression Analysis, Hypothesis Test, and Classical Assumption Test. Based on this research, the results show that Tax Avoidance and Net Profit Margin affect the stock price, while Institutional Ownership and Earning Per Share do not affect the stock price.